Space time block codes with turbo codes - Torres, Paulo (2011)
This paper aims to provide efficient solutions to improve the power efficiency, like implementation of schemes using MIMO (Multiple-Input Multiple-Output), with error correction codes. Thanks to the union of these two techniques is possible to obtain a low error probability with low power consumption. This paper shows STBC (Space Time Block Codes) with codes and diversity in the reception using a MRC (Maximum Ratio Combining). In this solution are studied Alamouti codes [1] and those proposed by Tarokh et al [2], with four and eight transmit antennas. Turbo Codes are used in the decoding algorithm with soft output, the log-MAP. The simulation results of the performance of error probability (BER) are performed in MATLAB with 4-QAM modulation in a Rayleigh channel.